The limits to profit-wage redistribution: Endogenous regime shifts in Kaleckian models of growth and distribution - Kasper Köhler (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
A feature of Kaleckian models of distribution and growth that is often overlooked is that they describe a nonlinear relation between functional income distribution and demand and growth, because the size of the multiplier is affected by redistribution from wages to profits and vice versa. This paper addresses the nonlinearity of the standard post-Kaleckian model by examining its so-called IS-curves. It is found that changes in functional income distribution affect the "distribution-ledness" of an economy: redistribution towards wages reinforces the wage-led or profit-led character of an economy, while redistribution towards profits does the opposite. In addition, redistribution towards wages can turn an intermediate regime wage-led. A standard post-Kaleckian model with nonlinear investment behaviour is then presented. This model yields substantially different IS curves, such that an optimal functional income distribution can be derived. However, it is found that unlike in the standard model, this optimum is not the same for the different classes, such that true opposing interests appear in the model.
Keywords: B59; E11; E12; E25; O40; 330; distribution; growth; nonlinearity; demand and growth regimes; Kaleckian models